Hospital readmissions after catheter ablation for atrial fibrillation among patients with heart failure in the United States. (25th November 2020) - Lima, F; Kennedy, K; Parulkar, A; Sheikh, W; Sharma, E; Chu, A
Abstract: Background: Catheter ablation for atrial fibrillation may improve quality of life and long-term mortality among patients with heart failure. Purpose: The rates of hospital readmission after catheter ablation for atrial fibrillation among patients with an established diagnosis of heart failure are largely unknown. We aimed to assess the rates and causes of 30-day readmission among patients with heart failure undergoing catheter ablation vs. medical therapy for atrial fibrillation in the United States. Methods: The 2016 Nationwide Readmissions Database was screened for patients with diagnosis of heart failure and atrial fibrillation using the 10th Revision of International Classification of Diseases codes. Patients undergoing catheter ablation for atrial fibrillation were grouped separately from those treated medically for atrial fibrillation. Thirty-day readmissions were assessed for both groups. Results: The analytical cohort included 749, 776 (national estimate of 1, 421, 673) patients with heart failure and atrial fibrillation. This included 2, 204 patients that underwent catheter ablation. Patients treated with catheter ablation had lower 30-day readmissions compared to the medical therapy group (16.8% vs 20.1%, p<0.001). Fifty-five percent of all readmissions among the catheter ablation cohort were related to cardiac events. Heart failure exacerbation (40%) and arrhythmia (36%) were the most common cardiac causes for readmission after catheter ablation (Figure). Conclusions: In a contemporary nationwide analysis of patients with heart failure and atrial fibrillation, compared to medical therapy those treated with catheter ablation for atrial fibrillation had fewer 30-day readmissions after index hospital discharge. The most common cause for readmission among patients treated with catheter ablation was heart failure exacerbation and arrhythmia. Funding Acknowledgement: Type of funding source: None